2013
DOI: 10.1128/genomea.00544-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Enterobacter sp. Strain R4-368, an Endophytic N-Fixing Gammaproteobacterium Isolated from Surface-Sterilized Roots of Jatropha curcas L

Abstract: Enterobacter sp. strain R4-368 is one of the few characterized Jatropha endophytic diazotrophic bacteria and was isolated from surface-sterilized roots. This bacterium shows strong growth-promoting effects, being able to increase plant biomass and seed yields. Enterobacter sp. R4-368 is the second fully sequenced diazotrophic Enterobacter species. The sequence information shall facilitate the elucidation of the molecular mechanisms of plant growth promotion, nitrogen fixation in nonlegume plant species, and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…E. asburiae was isolated from mustard rhizosphere soil which was reported as fungicide tolerant and endowed with PGP traits ( Ahemad and Khan, 2010 ). Madhaiyan et al (2013) reported the complete genome sequence of Enterobacter sp. strain R4-368, an endophytic N-fixing γ-proteobacterium isolated from surface sterilized roots of Jatropha curcas L. showing strong growth-promoting activity by increasing plant biomass and seed yields.…”
Section: Discussionmentioning
confidence: 99%
“…E. asburiae was isolated from mustard rhizosphere soil which was reported as fungicide tolerant and endowed with PGP traits ( Ahemad and Khan, 2010 ). Madhaiyan et al (2013) reported the complete genome sequence of Enterobacter sp. strain R4-368, an endophytic N-fixing γ-proteobacterium isolated from surface sterilized roots of Jatropha curcas L. showing strong growth-promoting activity by increasing plant biomass and seed yields.…”
Section: Discussionmentioning
confidence: 99%
“…The genome of the strain R4-368 comprises a single circular chromosome of 5,039,027 bp with 54.0% GC content (deposited in GenBank under the accession number CP005991) and one plasmid pENT01 of 116,007 bp with 52.8% GC content (deposited in GenBank under the accession number CP005992) [13]. …”
Section: Comparison With the Genome Of Enterobacter Sp Strain R4-368mentioning
confidence: 99%
“…monteilii and other well represented species in Ugt such as Klebsiella variicola , and Enterobacter sp. R4-368 were first isolated from clinical samples and treated as potential human pathogens [ 76 ], they also have been shown to be nitrogen fixers when living as plant-associated bacteria [ 77 , 78 ] and providing other plant benefits like phosphorus mobilization, fungi pathogen inhibition, and providing plant hormones to its host [ 79 – 81 ]. Previous reports on the model Arabidopsis have highlighted the thin line between being a pathogen or a beneficial bacterium.…”
Section: Resultsmentioning
confidence: 99%